An evaluation of systematic errors on marker-based registration of computed tomography and magnetic resonance images of the liver. (July 2018) - Woolcot, Thomas; Kousi, Evanthia; Wells, Emma; Aitken, Katharine; Taylor, Helen; Schmidt, Maria A.
Abstract: We demonstrated a general method to evaluate systematic errors related to Magnetic Resonance (MR) imaging sequences in marker-based co-registration of MR and Computed Tomography (CT) images, and investigated the effect of MR image quality in the co-registration process using clinical MR and CT protocols for stereotactic ablative body radiotherapy (SABR) planning of the liver. Small systematic errors (under 1.6 mm) were detected, unlikely to be a clinical risk to liver SABR. The least favourable marker configuration was found to be a co-planar arrangement parallel to the transaxial image plane.